The Implementation of Scientific Approach for Cooperative Learning Model Typed Inside Outside Circle (IOC) Toward the Science Learning Outcomes of the Seventh Graders of Lawang Public Islamic JHS Mandahiling - Maiyena, Sri; Khaira, Kuntum; Oktavia, Widia (Impulse: Journal of Research and Innovation in Physics Education, 2021)
The science learning outcomes of grade VIII students at MTsN Lawang Mandahiling are still low. Students physics's low learning outcomes are because teachers still dominate physics learning, and the intensity of student involvement when learning is a little. This study aims to determine how to apply a scientific approach to the Inside-Outside Circle cooperative learning model for students' physics learning outcomes. This type of research is quasi-experimental research, with the research design used is posttest only control group design. Sampling used random sampling, resulting in two sample classes, namely class VIII.2 as the experimental and VIII.3 as the control class. The data collection used a test of student learning outcomes on knowledge competencies in a multiple-choice test of 20 items. The competency data of students' attitudes and skills used observation sheets which were analyzed qualitatively descriptive. The results of the final tests conducted in the study showed that the physics learning outcomes of students in the experimental class were better than the control class. The average final score of students for knowledge competence in the experimental class and control class, respectively, was 78.00 and 66.00. For attitudinal competence, the average scores obtained by the experimental class and control class were 68.98 and 65.34, respectively. For the competency skills, the average scores obtained by the experimental class and control class are 74.22 and 68.25, respectively. Hypothesis testing is done by using a t-test. From the calculation on knowledge competency, the result of tcount = 3.07 while ttable = 1.684; on attitude competence, the price of tcount = 2.29; on skills competency, the tcount = 4.26; while ttable = 1.684 while t table = 1.684 at the real level α = 0.05. It means that tcount> ttable so that H0 is rejected and H1 is accepted. It can be concluded that the students' physics learning outcomes in applying the synthetic approach to the Inside-Outside Circle cooperative learning model are better than the physics learning outcomes of students who do not use the Inside-Outside Circle cooperative learning model in solar system subject matter in grade VIII MTsN Lawang Mandahiling.